Enhancing ovulation of Malaysian mahseer (Tor tambroides) in captivity by removal of dopaminergic inhibition - Nik Daud, Nik Md. Azuadi; Siraj, Siti Shapor; Daud, Siti Khalijah; Christianus, Annie; Harmin, Sharr Azni; Sungan, Stephen; Britin, Raymond (Academic Journals, 2011)
Natural spawning ground of most Malaysian streams are undergoing extreme changes as a result of human activities, pollution and climate change (extreme temperature fluctuation) which lead to dramatic decrease in mahseer (Tor tambroides, Cyprinidae) populations. An experiment was conducted to evaluate the effectiveness of salmon gonadotropin releasing hormone analogue (sGnRHa) alone or in combination with dopamine antagonist domperidone (DOM) on breeding performances of female breeders. Sixty females T. tambroides ranging in weight 2.01 to 3.96 kg while thirty males with average weight 1.38 to 1.72 kg were used in this study. The females were given pretreatment with Ovaplant (23.4-44.9 μg kg-1) for 6 weeks prior to induction. Females were tested with various treatments such as Ovatide, sGnRHa, sGnRHa+DOM and DOM. SGnRH analogue alone does not contain dopamine antagonist to block dopaminergic inhibition action. Females were given single intramuscular injection of Ovatide (0.5 mL kg-1 BW), sGnRHa (10 μg kg-1 BW), sGnRHa+DOM (10 μg kg-1 BW+5 mg kg-1 BW) or DOM (5 mg kg-1 BW). The control group was administered with 0.9% NaCl. The fish did not spawn spontaneously but through hand stripping to release eggs. Results showed that Ovatide significantly produced highest ovulation rate, total stripped eggs and stripped fecundity. Interestingly, we observed that broodstock groups injected with sGnRHa+DOM produced highest fertilization, hatching and survival rates compared to other treatments. Good egg and larval quality were recorded in the group treated with sGnRHa+DOM. No females ovulated in the group receiving DOM alone and saline solution. The combination treatment was found to be more potent in inducing ovulation as compared to sGnRHa alone or DOM alone. Our results suggest that dopaminergic inhibition is a major barrier in inducing spontaneous spawning in captive mahseer and we successful produced progeny generation of T. tambroides larvae.